Asymptotic normality of fluctuations of the procedure of stochastic approximation with diffusive perturbation in a Markov medium - Chabanyuk, Ya. M. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We consider the asymptotic normality of a continuous procedure of stochastic approximation in the case where the regression function contains a singularly perturbed term depending on the external medium described by a uniformly ergodic Markov process. Within the framework of the scheme of diffusion approximation, we formulate sufficient conditions for asymptotic normality in terms of the existence of a Lyapunov function for the corresponding averaged equation.